No effect of carbohydrate-protein on cycling performance and indices of recovery - Breen, L.; Tipton, K. D.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2010)
The aim of this study was to determine whether adding protein to a CHO beverage would improve late-exercise cycle time-trial performance over CHO alone. Furthermore, we examined the effects of coingesting protein with CHO during exercise on postexercise markers of sarcolemmal disruption and the recovery of muscle function.